Faktor-Faktor yang Memengaruhi Keuntungan Usaha Tani Tembakau di Kecamatan Manisrenggo Kabupaten Klaten - Rachmanindita, Zurinda Adkha; Handayani, Sugiharti Mulya; Rahayu, Wiwit (Program Studi Magister Agribisnis, Universitas Sebelas Maret, 2022)
The agricultural sector, especially plantations, has entered the business world that considers profit in its activities. One of them is tobacco farming in Manisrenggo Sub-district, Klaten Regency. This study aims to determine the costs, revenues, income, and profits of tobacco farming, and what factors affect the profits of tobacco farming in Manisrenggo Sub-district, Klaten Regency. The method used in this research is descriptive analytical purposive location determination, and sampling using random sampling method. The data were analyzed by farming and multiple linear regression. The results showed that the average revenue from tobacco farming was IDR22,377,755.40 per planting period per ha, the total cost was IDR12,486,217.36 per planting period per ha, the income was IDR12,023,202.48 per planting period per ha, and the profit was IDR9,974,588.43 per planting period per ha. Factors that have a significant effect on the profits of tobacco farming are land area and production costs with positive coefficient values. The level of education has a negative and significant effect on the profits of tobacco farming.